2016
DOI: 10.1016/j.scienta.2016.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ‘Subirana’ flat peach cultivar budded on different Prunus rootstocks in a warm production area in North Africa

Abstract: The agronomic performance and fruit quality traits were evaluated for ten Prunus rootstocks: Garnem, PADAC 150, PADAC 04-03, PADAC 04-01, Rootpac® 70, PM 105 AD, AGAF 0301-04, Krymsk® 1, Krymsk® 86 and PAC 847. These rootstocks were budded with 'Subirana' flat peach cultivar in September 2007 and planted in two adjacent plots in northern Tunisia (36°41'N, 10°15'E) on a heavy and calcareous soil typical of the Mediterranean area. Tree mortality, vegetative growth, rate of bud failure and fruit quality were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 45 publications
(77 reference statements)
1
8
0
1
Order By: Relevance
“…However, the overall yield average observed in the present study resembles that found in southern Brazil (Barreto et al, 2017), northern Tunisia (Yahmed et al, 2016) and northern and southern Italy (Scalisi et al, 2018). (Zarrouk et al, 2006;Neves et al, 2017) and in pear (Melo et al, 2017), in order to introduce useful characteristics such as vigor control, pest resistance and edaphoclimatic adaptation, such a combination does not always result in success.…”
Section: Heritability Of Individual Plots Average Genotype Heritabilsupporting
confidence: 59%
“…However, the overall yield average observed in the present study resembles that found in southern Brazil (Barreto et al, 2017), northern Tunisia (Yahmed et al, 2016) and northern and southern Italy (Scalisi et al, 2018). (Zarrouk et al, 2006;Neves et al, 2017) and in pear (Melo et al, 2017), in order to introduce useful characteristics such as vigor control, pest resistance and edaphoclimatic adaptation, such a combination does not always result in success.…”
Section: Heritability Of Individual Plots Average Genotype Heritabilsupporting
confidence: 59%
“…This cluster showed that the rootstocks were not grouped according to their genetic origin, although results confirm that the plum based hybrids "PADAC 04-01" and "PADAC 99-05" induced fruits with the higher values on SSC and several color parameters (L*, b*, C*, and h). In a rootstock trial established in a peach production area of Tunisia, the hybrid "PADAC 04-01" induced also a good agronomical performance and higher fruit quality (SSC) compared to other nine rootstocks budded with the flat peach "Subirana" [10], confirming its suitability for the Mediterranean area.…”
Section: Effect Of Rootstock On Fruit Quality Traitsmentioning
confidence: 87%
“…Agronomy 2020, 10, x; doi: www.mdpi.com/journal/agronomy grouped according to their genetic origin, although results confirm that the plum based hybrids "PADAC 04-01" and "PADAC 99-05" induced fruits with the higher values on SSC and several color parameters (L*, b*, C*, and h). In a rootstock trial established in a peach production area of Tunisia, the hybrid "PADAC 04-01" induced also a good agronomical performance and higher fruit quality (SSC) compared to other nine rootstocks budded with the flat peach "Subirana" [10], confirming its suitability for the Mediterranean area. In general, the plums "Adesoto 101" and "PM 105 AD", the peach-almond "Adarcias" and the interspecific plum based hybrids "PADAC 04-01", "PADAC 99-05" and "Rootpac R", showed the tendency to induce a better fruit quality, based on higher concentration of SSC, and other yield traits (Tables 5 and 6), demonstrating their commercial interest as rootstocks for peaches.…”
Section: Effect Of Rootstock On Fruit Quality Traitsmentioning
confidence: 87%
See 1 more Smart Citation
“…Há também um baixo controle relativo à identidade dos porta-enxertos, graças à adoção aleatória de sementes de cultivares copa, principalmente na maioria dos viveiros do Estado do Rio Grande do Sul (MAYER; BIANCHI e CASTRO, 2014). Assim, possíveis vantagens trazidas pelos porta-enxertos não são aproveitadas, como aquelas relacionadas a aumento ou diminuição do vigor e teor de nutrientes nas folhas (MAYER; UENO e SILVA, 2015), precocidade de produção , qualidade de frutos (PÉREZ-ROMERO et al, 2014;YAHMED et al, 2016), resistência a pragas e doenças , adaptabilidade a diferentes condições de solo, como fertilidade, salinidade e teor de água (JIMÉNEZ et al, 2011;KUCUKYUMUK et al, 2015;YADOLLAHI, 2011), produtividade (YAHMED et al, 2016), dentre outras.…”
Section: Introductionunclassified